2019
DOI: 10.1038/s41420-019-0199-x
|View full text |Cite
|
Sign up to set email alerts
|

DRP-1 functions independently of mitochondrial structural perturbations to facilitate BH3 mimetic-mediated apoptosis

Abstract: Maintenance of mitochondrial integrity is critical for normal cellular homoeostasis. Most cells respond to stress stimuli and undergo apoptosis by perturbing mitochondrial structure and function to release proteins, such as cytochrome c , which are essential for the execution of the intrinsic apoptotic cascade. Cancer cells evade these events by overexpressing the anti-apoptotic BCL-2 family of proteins on mitochondrial membranes. Inhibitors of the anti-apoptotic BCL-2 family proteins, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…release of proteins, changes in mitochondrial morphology, loss of ΔΨ m ), only a few studies have investigated the role of Drp1 in mitochondria integrity. Milani and coworkers showed that several BH3 mimetics (ABT-199, A1331852, A1210477) induced mitochondrial fission and apoptosis in a Drp1dependent manner (Milani et al 2019(Milani et al , 2017. Appropriately, the treatment of human cardiomyocytes with the MCL-1 inhibitor S63845 resulted in Drp1-dependent mitochondrial fragmentation (Rasmussen et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…release of proteins, changes in mitochondrial morphology, loss of ΔΨ m ), only a few studies have investigated the role of Drp1 in mitochondria integrity. Milani and coworkers showed that several BH3 mimetics (ABT-199, A1331852, A1210477) induced mitochondrial fission and apoptosis in a Drp1dependent manner (Milani et al 2019(Milani et al , 2017. Appropriately, the treatment of human cardiomyocytes with the MCL-1 inhibitor S63845 resulted in Drp1-dependent mitochondrial fragmentation (Rasmussen et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…While the stability of OPA-1 is decreased and fusion is repressed, MCL1 does not abolish its activity as mitochondria can still undergo fusion when MCL1 is inhibited 128 . Subsequent studies have since shown that MCL1-specific BH3 mimetics display fragmented mitochondrial networks, highlighting the shift in mitochondrial dynamics toward enhanced organelle fragmentation through fission 117,131,132 (Fig. 4c).…”
Section: Mcl1 Facilitates Mitochondrial Bioenergetics and Dynamicsmentioning
confidence: 92%
“…Both proteins can be co-localized with Bax at the MOM, with Drp1 being recruited by Bax after apoptosis induction, promoting fission; and Mfn2 binding to Bax, leading to mitochondrial fusion inhibition [52,53,66,67]. Furthermore, Drp1 plays an essential role in cytochrome c release and in pro-apoptotic Bak activation [51,68]. Downregulation or blocking of Drp1 has been shown to have anti-apoptotic effect in different in vitro models [53,[68][69][70].…”
Section: Mitochondrial Dynamics and Apoptosismentioning
confidence: 99%
“…Furthermore, Drp1 plays an essential role in cytochrome c release and in pro-apoptotic Bak activation [51,68]. Downregulation or blocking of Drp1 has been shown to have anti-apoptotic effect in different in vitro models [53,[68][69][70]. Of note, apoptosis can occur without mitochondrial fragmentation, with some studies showing that blocking fission only slows down apoptosis rather than entirely preventing it [53,68,71,72].…”
Section: Mitochondrial Dynamics and Apoptosismentioning
confidence: 99%